2006
DOI: 10.1007/s00248-006-9086-0
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium Mycobiota in Arctic Subglacial Ice

Abstract: Fungi have been only rarely isolated from glacial ice in extremely cold polar regions and were in these cases considered as random, long-term preserved Aeolian deposits. Fungal presence has so far not been investigated in polar subglacial ice, a recently discovered extreme habitat reported to be inhabited exclusively by heterotrophic bacteria. In this study we report on the very high occurrence (up to 9000 CFU L(-1)) and diversity of filamentous Penicillium spp. in the sediment-rich subglacial ice of three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 34 publications
1
53
0
1
Order By: Relevance
“…Species of the genus Penicillium belonging to the subgenus Furcatum are efficient producers of metabolites and the extrolite patterns are effective markers for species recognition (Frisvad & Filtenborg, 1990;Tuthill et al, 2001;Sonjak et al, 2007). We found that each novel species produced unique and characteristic patterns of known and uncharacterized metabolites; an overview is given in Table 2.…”
Section: Extrolite Analysismentioning
confidence: 88%
“…Species of the genus Penicillium belonging to the subgenus Furcatum are efficient producers of metabolites and the extrolite patterns are effective markers for species recognition (Frisvad & Filtenborg, 1990;Tuthill et al, 2001;Sonjak et al, 2007). We found that each novel species produced unique and characteristic patterns of known and uncharacterized metabolites; an overview is given in Table 2.…”
Section: Extrolite Analysismentioning
confidence: 88%
“…P. crustosum was unable to produce large lesions at the cold storage conditions tested compared to the big lesions under room storage conditions. Penicillium spores are able to tolerate extremely low temperature conditions and germinate when conditions become favourable for growth (24,27). …”
mentioning
confidence: 99%
“…Such type of fungi have been found and investigated in all major cold habitats, such as Antarctica (Blanchette et al, 2010), Arctic regions (Sonjak et al, 2006) and cold deep sea environments (Damare et al, 2006). Various fungi representing different genera and species e.g.…”
Section: Introductionmentioning
confidence: 99%